Software Server for Automatic Generation of Audio Lectures (uListenSrv) - Petrov, Milen; Asenov, Asen; Aleksieva-Petrova, Adelina (International Journal of Advanced Corporate Learning (iJAC), 2017)
Facilitation of new methods for learning materials delivery and adoption of new learning experiences and practices in e-learning is always a challenge. Using synthesis of digital audio learning assets and learning objects as one of main sources for conducting learning is not new, but research on using audio lectures or combined audio with presentation lecture is not well investigated and adopted in traditional online learning environments. The main goal of current paper is to present requirements elicitation, software analysis, design, construction and testing of secure and reusable software architecture for production and delivery of learning resources with audio elements in university programming courses. Paper presents different architecture styles for designing the system and finish with presentation of development and usage of contemporary Software Server for Automatic Generation of Audio Lectures (uListenSrv). Main difference here is support of languages, not only in English, but not so popular languages, like Bulgarian language.